2014
DOI: 10.4236/health.2014.616256
|View full text |Cite
|
Sign up to set email alerts
|

Adopting Health Apps, What’s Hindering Doctors and Patients?

Abstract: There are high expectations for Mobile Health to transform health into a sustainable and prevention-based system. Unfortunately it has not reached its scale of adoption many had hoped for, due to the existence of adoption barriers. More insight into these barriers fosters adoption of mHealth and the innovation it can bring to worldwide healthcare. This study investigates the main barriers in the adoption of mHealth, their underlying causes and their breakthrough possibilities. All the data are gathered from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…However, users and developers rank the importance lower than policy-makers. This might be since users, such as doctors, benefit from the current payment mechanism; consequently they might not perceive it as an important barrier [134].…”
Section: Barriers and Challengesmentioning
confidence: 99%
See 4 more Smart Citations
“…However, users and developers rank the importance lower than policy-makers. This might be since users, such as doctors, benefit from the current payment mechanism; consequently they might not perceive it as an important barrier [134].…”
Section: Barriers and Challengesmentioning
confidence: 99%
“…Telehealth, in its more general sense, enables the delivery of healthcare services directly to the home environment of the patients, extending and enhancing the level of care [291]. Actually, in the last decades several works have showed that using Information Technologies (IT) on health domain reached positive conclusions [134]. For chronic and long-term disease management telehealth offers a broad range of potential tools that can enhance the health outcomes and effectiveness of the care delivery.…”
Section: Health Technology Assessmentmentioning
confidence: 99%
See 3 more Smart Citations